A Critical Review of Russia's Energy Strategy in the Period until 2035 - Alekseev, Alexander N.; Bogoviz, Aleksei V.; Goncharenko, Ludmila P.; Sybachin, Sergey A. (International Journal of Energy Economics and Policy, 2019)
Noting the enormous importance of the Russian and energy complex for international and domestic energy policies, the paper critically reviews the Energy Strategy of Russia until 2035, focusing on the state, challenges, and development trends of the global and Russian energy. We devote a lot of attention to the internal problems and export opportunities, the key aspects of the Russian energy policy in long-term perspectives, as well as review the development scenarios and stages of implementation. While conducting a critical review, we focus on how well the Strategy captures the current situation in international energy markets and trends in the development of the Russian energy and fuel complex. We also look into how comprehensively the Strategy addresses the identified challenges and possible prospects, as well as discuss which provisions could strengthen the Strategy. Our analysis clearly demonstrates that the Strategy adequately addresses both international and domestic processes leading to the current state of the Russian fuel and energy complex. However, we also point out to a number of shortcomings. First, it still supports the export-oriented model of energy development in Russia, but it would be much promising to focus on building a model of resource-innovative development. Second, there is no comprehensive strategy of working on the European energy market and the markets of the Asia-Pacific region, and the proposed scenarios do not take into account the shrinking export demand in the future. Third, it primary focuses on the carbon resources, not providing sufficient attention to the increasing role of renewable energy. Fourth, the outlined ambitious plans of technological modernization of the refinery sector appear hard to implement in the current conditions of protracted technological development and technological sanctions. These identified drawbacks could be used for developing policy recommendations. Keywords: Energy Policy, Energy Strategy, Fuel and Energy Complex, Russia JEL Classifications: Q2, Q3, Q4 DOI: https://doi.org/10.32479/ijeep.8263